Migration timespaces: a Heideggerian approach to understanding the mobile being of Eastern Europeans in Scotland - Sergei Shubin (Transactions of the Institute of British Geographers, 2015)
This paper studies timespaces of migrants from Eastern Europe, who come to settle to Scotland. Using philosophical analysis from Martin Heidegger’s works (Being and time, The Yster, Contributions to philosophy), it develops a broader conceptualisation of timespaces, which moves beyond ‘neatly mappable’ life course geographies of migration. It uses relational understanding of time-space, situatedness and potentiality of movement to develop an ‘integrative’ approach which brings together objective and subjective timespaces of migration.